Ruang Kurban App: As a virtual reality (VR) Qurban of Simulation Application in Children's Learning Media - Hendri Herdiansyah; Muhammad Indana Zulfa; Muhammad Taufik Hidayat P (Universitas Komputer Indonesia, 2022)
The development of a technological progress that is so very fast from ancient times until now, cannot be simply rejected, ranging from agriculture, social, culture to education which really helps all human activities become more efficient, one of the developments of this technological progress in the field of education is making innovations in the field of education, interactions become more diverse, such as where one of them is Virtual Reality (VR) technology in the form of applications on smartphones. The purpose of this research is to help the progress of education with the application of a sacrifice simulation that will be made as a learning medium for children. The research method that we use in our journal is a qualitative method, the results of this study make the application of qurban simulation to increase children's interest in learning in religious matters, namely understanding qurbani in a more different way. The main concept in this application is to present virtual reality regarding the simulation of sacrifices as a medium for children's learning. In the conclusion of this study, therefore with this application, virtual reality sacrifice applications can be made as children's learning media and help teachers in each school to teach and with this application children can feel directly in the form of virtual reality